2017
DOI: 10.1097/nmc.0000000000000369
|View full text |Cite
|
Sign up to set email alerts
|

Status of High Body Weight Among Nurse-Family Partnership Children

Abstract: Moderation of weight gain during pregnancy, extending breastfeeding duration, and normalization of BMI before subsequent pregnancies may potentially serve as means of lowering the prevalence of high body weight levels in young children of low-income families served by home visitors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Such findings, largely based on randomized trials, add further support to the potential for NFP to facilitate clients' growth toward economic self-sufficiency, as a result of the program's replication. Additionally, prior studies of other cohorts from NFP replications have also shown beneficial impacts on birth outcomes and child development metrics Thorland, Currie, & Colangelo, 2017;Thorland, Currie, Wiegand, et al, 2017).…”
Section: Discussionmentioning
confidence: 95%
“…Such findings, largely based on randomized trials, add further support to the potential for NFP to facilitate clients' growth toward economic self-sufficiency, as a result of the program's replication. Additionally, prior studies of other cohorts from NFP replications have also shown beneficial impacts on birth outcomes and child development metrics Thorland, Currie, & Colangelo, 2017;Thorland, Currie, Wiegand, et al, 2017).…”
Section: Discussionmentioning
confidence: 95%
“…More than two-thirds of pregnant women exceed the Institute of Medicine (IOM) 2009 gestational weight gain (GWG) recommendations [1–3]. Excess gestational weight gain is problematic for women entering pregnancy at any size [4], and pregnant women with overweight and obesity are at increased risk for adverse maternal outcomes including gestational diabetes, hypertension [5, 6], Cesarean delivery [6, 7], and postpartum weight retention [2, 8], and infant outcomes including large for gestational age at birth [9] and obesity in childhood [10, 11]. Limiting gestational weight gain as recommended by the IOM guidelines may, therefore, have beneficial effects for both mother and infant at delivery and later in life highlighting the critical need for interventions promoting appropriate weight gain during pregnancy [12].…”
Section: Introductionmentioning
confidence: 99%
“…More than 40% of low-income children enrolled in federally funded programs are overweight or obese by age 5 [43–46] Recent data further indicates that the prevalence of high Weight-For-Length among children enrolled in home visitation programs is substantially greater than that of the general U.S. population (based on NHANES data). This trend also persisted across strata based on the sex of the child, as well as across primary classifications of race-ethnicity [133] Given the high prevalence of obesity in this priority population, childhood obesity will likely be identified as a priority to be addressed by home visitation programs nationwide. These priorities are set forth by the funder of our home visitation partner for this project (U.S. Maternal Infant and Early Childhood Home Visiting Program; Health Resources and Services Administration; U.S. Department of Health and Human Services).…”
Section: Resultsmentioning
confidence: 99%